AYURVEDIC ENTREPRENEURSHIP IN THE DIGITAL ERA: STARTUPS, INNOVATION, AND SUSTAINABLE GROWTH THROUGH TRADITIONAL KNOWLEDGE SYSTEMS - Dr. Parag Vishwas Kulkarni; Dr. Amar Baliram Abhrange (International Educational Journal of Science and Engineering, 2025)
The twenty-first century has witnessed an unprecedented rise of startups, digital technologies, and sustainability-driven innovation. Within this dynamic ecosystem, Ayurveda, one of the oldest systems of holistic healthcare, offers a unique platform for entrepreneurship and innovation. This paper explores the intersection of Ayurvedic knowledge, modern startup ecosystems, and digital transformation in fostering sustainable growth. Drawing on classical Ayurvedic concepts such as Hetu, Nidan Parivarjan, and preventive medicine, alongside contemporary entrepreneurial practices, the study emphasizes how traditional medical wisdom can be adapted into viable business models. Key themes include AI-driven diagnostic platforms, digital health consultation, herbal product manufacturing, financing models for startups, government policies, and global opportunities for Ayurvedic businesses. Case studies of successful ventures and lessons from failures are analysed to highlight practical implications. The findings underscore that integrating Ayurveda with artificial intelligence, digital tools, and sustainable innovation creates opportunities not only for economic growth but also for global wellness and environmental conservation. Ultimately, the fusion of Ayurveda and entrepreneurship aligns with the principles of resilient business ecosystems and the United Nations Sustainable Development Goals (SDGs).